Moringa oleifera: A Comprehensive Review of Its Nutritional Value and Medicinal Potential (Research in Agriculture Livestock and Fisheries, 2025)
Moringa oleifera is a versatile, nutritionally rich plant that has attracted global attention for its exceptional nutritional value and wide range of medicinal applications. Commonly known as the drumstick tree, horseradish tree, or miracle tree, M. oleifera is widely distributed across tropical and subtropical regions of the world. The plant is highly adaptable, capable of withstanding severe drought and mild frost, which has contributed to its extensive cultivation. Moringa oleifera is a small to medium-sized tree, typically growing 5–10 m in height, and almost every part of the plant is utilized for nutritional or medicinal purposes. This seminar paper is a narrative review based exclusively on secondary data obtained from published scientific literature and other reliable sources. Beyond being a rich source of proteins, vitamins, essential oils, fatty acids, macro- and micro-minerals, and phenolic compounds, M. oleifera has been reported to exhibit a broad spectrum of pharmacological activities, including anti-inflammatory, antidiabetic, antimicrobial, antioxidant, anticancer, cardioprotective, anti-ulcer, diuretic, and antiurolithiatic effects. These diverse therapeutic properties underpin its extensive use in traditional medicinal systems for the management of various diseases. The accumulated evidence highlights M. oleifera as a promising medicinal plant with significant potential for incorporation into modern healthcare systems. Further scientific investigation, including clinical and pharmacological validation, is warranted to fully elucidate its therapeutic efficacy and safety. This review underscores the need for a systematic and evidence-based appraisal of M. oleifera to establish its pharmaceutical potential in contemporary medicine.Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 555-565